(untitled) (Medico Legal Update, 2021)
Suicide is an imperative public health problem that needs social as well as medical attention. In India, 134516 people committed suicide in 2018 and also there is an increase in the number of suicide cases in Uttarakhand as well. The aim was to analyse the trend of suicidal deaths autopsied at our center concerning different parameters like age, gender, method of suicide, reason for suicide, to know the demographic pattern and its cause. The autopsy reports and inquest papers of suicidal cases autopsied at AIIMS Rishikesh were included for evaluation. Out of total 19.49% of total autopsies were of suicidal deaths. Majority of the victims were males (76.42%) compared to females (22.76%). The average age of victims was 35 years and 76.4% belonged to the age group 14 to 43 years. The risk of suicide was more prevalent in urban population. Among the total victims, 39.83% were in jobs. Regarding the reason behind suicide, family dispute was most common. The most common mode of suicide was hanging followed by poisoning and drowning. Organophosphates was the most repeated poison consumed in suicides by poisoning. About 75% cases were complete suicides and couldn’t receive medical care. Majority of the cases belonged to Rishikesh police station. The important aspects of suicides among young generation is peer pressure which can be from family, institutional, or work etc. An effective strategy needs to be devised to combat the issue.